Clinical Outcome of Intravenous Immunoglobulin in the treatment of Guillain Barre Syndrome in a Nepalese Tertiary Centre (Nepalese Medical Journal, 2019)
Introduction: Intravenous Immunoglobulin is an approved therapy for Guillain Barre Syndrome. Our objective is to understand the management and outcome in Guillain Barre Syndrome patients treated with Immunoglobulin.Materials and Methods: All consecutive patients were retrospectively evaluated in the study were of age ≥16 years and were being admitted in the department of Neurology of Tribhuvan University Teaching Hospital, Kathmandu, Nepal from 2016 March to 2017 February.Results: A total of 46 patients were included, mean age= 36.5±16.2 years, range = 16years to 80 years. Thirty-two patients (70%) were axonal variant, acute motor axonal neuropathy is more common (18 patients). Intravenous immunoglobulin was used in 23 patients (50%), 17 of them were axonal variant and 6 were demyelinating. Guillain Barre Syndrome patients with bilateral facial weakness (70% vs 30%; p